Implementasi Sistem Peringatan Dini Banjir Berbasis IoT Menggunakan Raspberry Pi 3 dengan Notifikasi WhatsApp Real- Time - Theofilus Herly Hatonangan Samosir; Sugiyaanti (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Floods are common natural disasters in Indonesia, causing material damage and loss of life. One mitigation measure that can be implemented is to provide an early warning system capable of monitoring water levels in real time. The purpose of this research is to design and develop a flood early warning system that is based on the Internet of Things (IoT) with a Raspberry Pi as the central controller. This system uses ultrasonic sensors to measure water levels, where the measured data is processed by the Raspberry Pi and then sent to a website for live display. In addition, the system is also connected to the WhatsApp application to send automatic notifications to users when the water level reaches an alert or dangerous level. The methods applied in this research include hardware design, software development, system integration, and functionality testing. The test results indicate that this system can accurately monitor water levels and send alerts via WhatsApp with a quick response. The developed website is also capable of displaying real-time water level status, allowing users to monitor remotely. In this way, the designed system can serve as an alternative solution to support flood mitigation and early warning efforts.